2006
DOI: 10.1111/j.1600-0781.2006.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐band ultraviolet B phototherapy in zoster patients may reduce the incidence and severity of postherpetic neuralgia

Abstract: UVB phototherapy in the acute stage of zoster rash might reduce the incidence and severity of PHN. Treatment after 3 months does not seem to have a significant beneficial effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Figure 1 presents the process by which we identified 302 relevant studies in the four databases. After removing the duplicates, we screened 223 studies based on the titles and contents of the abstracts and excluded 214 that did not meet our inclusion criteria, leaving nine for further evaluation [ 43 , 52 , 53 , 67 , 75 , 76 , 77 , 78 , 79 ]. After examining the full texts of these articles, we excluded four clinical trials [ 50 , 76 , 77 , 80 ] because of a lack of a comparison group or of clarity regarding the number of PHN patients who received acyclovir.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 presents the process by which we identified 302 relevant studies in the four databases. After removing the duplicates, we screened 223 studies based on the titles and contents of the abstracts and excluded 214 that did not meet our inclusion criteria, leaving nine for further evaluation [ 43 , 52 , 53 , 67 , 75 , 76 , 77 , 78 , 79 ]. After examining the full texts of these articles, we excluded four clinical trials [ 50 , 76 , 77 , 80 ] because of a lack of a comparison group or of clarity regarding the number of PHN patients who received acyclovir.…”
Section: Resultsmentioning
confidence: 99%
“…McGill and White (1994) also reported that acyclovir could prevent the incidence of PHN [69]. However, other studies found that acyclovir did not prevent PHN [42,45,[70][71][72][73][74][75][76][77][78][79][80][81][82]. Beyond antiviral agents, as mentioned, there have also been reports that tricyclic antidepressants, topical capsaicin, gabapentin, oxycodone, pregabalin, long-acting opioids, and tramadol alleviated PHN, though the long-term and clinical benefits of these treatments remain uncertain [28,83].…”
Section: Introductionmentioning
confidence: 99%